49.6k views
3 votes
Solve the system using elimination.
2x + 18y = -9
4x + 18y = -27

1 Answer

3 votes

First, let's cancel out the x by multiplying 2x + 18y = -9 by -2.

-2 ( 2x + 18y = -9) = -4x -36y = 18

Then, we combine the two equations.

-4x + 4x = 0

18y - 36y = -18y

-27 + 18 = -9

Our new equation is -18y = -9.

Now, divide both sides by -18.

-18y / -18 = y

-9/ -18 = 1/2

y = 1/2

We can plug in a value for y since y = 1/2 now.

Let's use 2x + 18y = -9

Plug in y.

2x + 18(1/2) = -9

2x + 9 = -9

Then, subtract 9 from both sides.

2x = -18

Divide by 2.

2x/2 = x

-18/2 = -9

x = -9

Lastly, we can plug in both x and y values to see it works.

2(-9) + 18(1/2) = -9

-18 + 9 = -9

Therefore, the values of x and y does work.

x = -9

y = 1/2

User Reda Igbaria
by
5.7k points